Options for methane mitigation in China's rice sector - Yang, Jintao; Zhang, Yumei; Zhang, Ruizeng; Fan, Shenggen; Zhou, Sheng; Li, Yangyang; Wang, Bin; Yang, Xiaoguang; Chen, Kevin Z. (China Agricultural University, 2025)
Methane emissions from rice cultivation in China reached 248 million tonnes of CO2equivalent (CO2eq), representing 26.6% of total agricultural greenhouse gas (GHG) emissions in 2021. Model simulations indicate that, due to a declining population and reduced rice consumption, methane emissions could decline by 15.9% in 2035 and by 35.4% in 2060, even without improvements in emission intensity reduction, driven primarily by a reduction in the cultivated area. Nevertheless, methane emissions from paddy fields remain a critical challenge for China in meeting its 2060 carbon neutrality target. Simulation results show that by 2035 and 2060, improved water management practices could reduce emissions by 20.4% and 32.4%, respectively; enhanced fertilizer and organic matter management by 10.6% and 16.8%, respectively; use of improved rice varieties by 3.5% and 6.9%, respectively; and optimized cultivation and tillage practices by 4.1% and 8.2%, respectively. A comprehensive mitigation strategy that integrates all of these measures could achieve total emission reductions by 39.1% in 2035 and by 63.8% in 2060. Despite the potential, scaling up these technologies faces several challenges. Many are still at the pilot or demonstration stage, with their effectiveness constrained by regional environmental conditions, low adoption rates, and insufficient technical support. Moreover, limited awareness, high technical complexity, and high implementation costs further hinder widespread uptake. Overcoming these barriers requires robust policy support, institutional innovation, and coordinated deployment of integrated technologies to facilitate scalable and sustained adoption.